THE PARADOXICAL IMPACT OF COMPANIONSHIP ON THE BIOPSYCHOSOCIAL HEALTH OF OLDER AFRICAN AMERICAN MEN - Mitchell, J. (Innov Aging, 2017)
Background: African Americans comprise 9% of the approximately 46 million U.S. adults age 65 and older. Two thirds of older African American (AA) men reside with spouses, relatives or other companions. This study investigated the assumption that living with or having frequent contact with companions most often confers health-related benefits for African American men. Methods: Utilizing a secondary data analysis of the National Alzheimer’s Coordinating Center Uniform Data Set, this investigation examined the relationship between older African American men’s physical health outcomes (diabetes, hypertension, cholesterol), mental health outcomes (depression, anxiety, sleep disturbances) and caregiver characteristics, including living arrangements and frequency of contact with the participants for 3,423 older AA men and their 1,161 companions at baseline. Findings: The mean age of both participants and companions was 74 years old and 90% of participants lived in a private residence. Logistic regression models indicated that the likelihood of high cholesterol was significant for participants when companions lived with participants (OR=1.38), called daily (OR=1.057) or visited daily (OR=1.059). Similar increased risk for anxiety was found when companions lived with (OR=1.66), called daily (OR=1.089), or visited daily (OR=1.079) with participants. Finally, participants experienced an increased likelihood of non-medical sleep disturbances when companions lived in (OR=1.67), called daily (1.105), or visited daily (1.078). All p-values were below .01. Conclusions: The frequency of contact with companions may be consequential for select health outcomes for older African American men, though the timing of contact (i.e. before any diagnosed illness or in response to it) requires further investigation.